O SPED e a racionalização das obrigações tributárias acessórias: promessa ou realidade? Um panorama das exigências tributárias instrumentais no âmbito do ICMS nos estados da Região Norte do Brasil a partir da implantação do SPED fiscal ICMS/IPI - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
The Sistema Público de Escrituração Digital (SPED) is a national macroproject which has as one of its objectives to promote the rationalization and simplification of accessory tax obligations. The Sped Fiscal ICMS/IPI, one of the subprojects of the SPED to be implemented, is the provision of various related information to ICMS, the main state tax, since the registration of tax documents relating to the operations and services practiced by the taxpayer to the detail the calculation of tax (including that relating to the tax substitution system) and other data related to the economic movement of the taxpayer. Thus, the Sped Fiscal ICMS/IPI has great potential to replace statements and information guides required by the Tax Administrations of the States (and the Federal District), thereby reducing the amount of accessory tax obligations. The objective proposed in this research was to analyze the effectiveness of Sped Fiscal ICMS/IPI as the effective rationalization of accessory tax obligations required of the ICMS taxpayers, with the study of the universe Tax Administrations of the States of Northern Brazil. This was an exploratory and descriptive study, which used as research tools bibliographical research, documentary research and survey, also being classified as a qualitative research on the problem approach. The results obtained showed that the implementation of the Sped Fiscal ICMS/IPI not contributed so far for an effective rationalization of the instrumental duties of ICMS taxpayers in the North Region.
Keywords: Escrituração Fiscal Digital; Tax Bookkeeping; Sistema Público de Escrituração Digital (SPED); Sped Fiscal; CIÊNCIAS SOCIAIS APLICADAS: ADMINISTRAÇÃO: CIÊNCIAS CONTÁBEIS